Effect of Various Oxidants on Reaction Mechanisms, Self‐Limiting Natures and Structural Characteristics of Al2O3 Films Grown by Atomic Layer Deposition. Issue 14 (26th April 2018) - Wang, Haoran; Liu, Yunfei; Liu, Hui; Chen, Zheng; Xiong, Pengpeng; Xu, Xiangchen; Chen, Fangyi; Li, Kun; Duan, Yu
Abstract: The present study investigates the Al2 O3 films grown by low‐temperature atomic layer deposition (ALD) with water vapor (H2 O), oxygen plasma (O2 plasma), and ozone gas (O3 ) serving as oxidants. The reaction processes with different oxidants are examined by in situ quadrupole mass spectrometry analysis of the gas phase species, which reveals a possible sequential reaction mechanism of trimethylaluminum and O2 plasma. The coefficient of standard deviation (CSD) of the oscillation frequency change of the in situ quartz crystal microbalance (Δ f ) to represent the self‐limiting nature of the films is used, and an obvious relationship is observed between the CSD of Δ f values and the density of ALD films, which suggests the intrinsic relationship between the structural characteristics and the self‐limiting natures of the ALD processes outside the temperature window. Fourier transform infrared spectroscopy reveals a large number of OCO, CO, and CH bonds remaining in the H2 O‐based Al2 O3 films, and the smallest concentration of carbon species is found to remain in the O3 ‐based Al2 O3 films, which explains the sources of the different self‐limiting natures and structural characteristics for the different oxidant‐based Al2 O3 films. Abstract : A method of using the coefficient of standard deviation of growth per cycle monitored by in situ quartz crystal microbalance to represent the degree of atomic layer deposition self‐limiting characteristics is presented. The relationship between different self‐limiting characteristics caused by various reaction mechanisms and other physical properties are precisely determined by this method.